2017
DOI: 10.1007/s11557-017-1332-y
|View full text |Cite
|
Sign up to set email alerts
|

Revision of species previously reported from Brazil under Morganella

Abstract: In our study, seventy-two specimens from Brazilian herbaria, New Zealand Fungal and Plant Disease Collection-PDD Herbarium, and the New York Botanical Garden Herbarium under Morganella were analyzed, including the paratype of M. mexicana and holotypes of M. arenicola, M. albostipitata, M. compacta, M. nuda, M. rimosa, and M. velutina. Specimens were studied morphologically following the literature for Morganella genus and for DNA extraction, amplification and molecular analyzes following literature such as Bru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Notes — The molecular analyses, based on ITS and LSU nrDNA sequences, obtained by Alfredo et al (2017) revealed Lycoperdon subg. Arenicola proposed here as the sister clade of L. subg.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notes — The molecular analyses, based on ITS and LSU nrDNA sequences, obtained by Alfredo et al (2017) revealed Lycoperdon subg. Arenicola proposed here as the sister clade of L. subg.…”
mentioning
confidence: 99%
“…Lycoperdon demoulinii can be clearly distinguished from L. arenicola since in L. demoulinii the exoperidium ornamentation is formed by big spines (0.6–1 mm long) that fall off leaving an endoperidium surface marked by areoles; while in L. arenicola these features are not present ( Alfredo et al 2014 , 2017 ). Lycoperdon americanum and L. echinatum are species morphologically similar to L. demoulinii in that they have the exoperidium ornamentation formed by spines, and the endoperidium surface is areolate; in L. demoulinii the spines are smaller than in L. americanum (3 mm long) ( Demoulin 1972 ) and L. echinatum (3–6 mm long) ( Demoulin 1983 , Calonge 1998 ).…”
mentioning
confidence: 99%
“…Studies carried out in the Neotropical region involving integrative taxonomy have revealed a great diversity of species hidden within cosmopolitan taxa and contributed to the description of new species and new genera (Alfredo et al 2017;Sousa, et al 2017;Accioly et al 2018;Accioly et al 2019;Cabral et al 2019;Sousa, et al 2019). These works, besides solving taxonomic conflicts, show the great diversity of species that remain undetected, especially in poorly sampled areas.…”
Section: Discussionmentioning
confidence: 99%
“…Lycoperdon is another genus that had recent changes in its classification. Due to the high morphological similarity between Lycoperdon and closely related genera, such as Morganella Zeller and Vascellum, many species were incorrectly identified, showing the need for molecular data to delimit species with higher reliability (Larsson and Jeppson 2008;Phosri et al 2014;Rusevska et al 2014;Alfredo et al 2017). Using molecular and morphological data, Alfredo et al (2017) also demonstrated the existence of new species and new combinations of previously identified materials, evidencing that there was a hidden diversity of Lycoperdon species under the name Morganella.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation